Individually Addressable Suspended Conducting‐Polymer Wires in a Chemiresistive Gas Sensor. Issue 17 (28th July 2014) - Chang, Won Suk; Kim, Jung Hyun; Kim, Daeho; Cho, Sung Ho; Kwon Seol, Seung
<x xml:space="preserve">Abstract</x> An effective method is described for producing poly(3, 4‐ethylenedioxythiophene) poly(styrenesulfonate) (PEDOT:PSS) arched microwires, which are used as transducers in chemiresistive gas sensors. Three‐dimensional arched wires with diameters of 0.8, 1.2, 2.5, and 10 μm are individually fabricated by using a simple, inexpensive fountain‐pen lithography technique. The wires show superior stretchable behavior under omnidirectional strain of ca. 120%. A gas sensor assembled with the PEDOT:PSS arched wires exhibits linear responses to the concentrations of different vapor gases, such as ethanol, acetone, and methanol, at room temperature. The signal‐to‐noise ratio in the sensing response, which influences the detection limit, is enhanced by increasing the number of wires with a larger surface‐to‐volume ratio in parallel to increasing the signal level and diminishing the baseline noise in the wire transducers. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>